WAYS OF ORGANIZING THE TEACHING OF THE SUBJECT OF FOLK PEDAGOGY BASED ON MODULAR TECHNOLOGIES - Rakhimberdiyeva Makhfuzakhan Murotovna (The Conference Hub, 2025)
This article explores innovative approaches to organizing the teaching of the subject of folk pedagogy in higher education through the use of modular technologies. As folk pedagogy represents the cultural, ethical, and traditional wisdom passed down through generations, its integration into modern education requires a pedagogical framework that is both flexible and culturally responsive. The study is based on qualitative research, incorporating document analysis, expert interviews, and classroom observations in selected Uzbek universities. The findings reveal that modular instruction enhances student engagement, deepens cultural awareness, and fosters critical and ethical thinking. Each module, centered on a specific cultural theme, allows for interdisciplinary exploration and localized content delivery. The study concludes that modular teaching not only preserves intangible cultural heritage but also transforms traditional content into dynamic, learner-centered experiences. Recommendations include the development of modular curricula, digital resources, and educator training programs to ensure the sustainable integration of folk pedagogy into contemporary educational practice.
Keywords: Folk pedagogy, modular teaching, cultural heritage, higher education, student engagement, interdisciplinary learning, educational innovation, Uzbekistan, curriculum development, teacher training.